(untitled) (Journal of Forensic Medicine & Toxicology, 2013)
What started as a major medico-legal dilemma in a University Health Centre in the South-West of Nigeria and which snowballed into a Coroner’s order for postmortem examination following a sudden and unexpected demise of a 22 year male after participating in a weekend campus social engagement, eventually ended as a natural disease. This case illustrates an unusual presentation of chronic myeloid leukaemia in a young male undergraduate student, who was otherwise healthy, in a university campus. It underscores the importance of thorough baseline clinical evaluation prior to admission into any institutions, and also emphasizes the essence of autopsy in all cases of sudden and unexpected deaths irrespective of circumstantial evidence and clinical diagnosis.